Monetary policy trade-offs and the correlation between nominal interest rates and real output - Moore, George R.; Fuhrer, Jeffrey C. (American Economic Review, 1995)
The authors present a structural model of the U.S. economy that combines their price-contracting specification with a term-structure relationship, an aggregate demand curve, and a monetary-policy reaction function. The model matches important features of postwar data well and provides a structural explanation of the correlation between real output and the short-term nominal rate of interest. The authors perform a battery of monetary-policy experiments that show that, as viewed through the lens of this model, monetary policy has struck a good balance recently among competing monetary-policy objectives. Copyright 1995 by American Economic Association.